ANALISIS YURIDIS PERSAMAAN HAK ANTARA PESERTA PENDIDIKAN DOKTER SPESIALIS DENGAN PEKERJA - Vinsensius Tommy Wijaya Japola (Arena Hukum, 2019)
AbstractParticipants in specialist medical education programs are one aspect that plays an important role in national development in the health sector. This is inseparable from one aspect of the specialist medical education program, which is service. Other countries such as the United States and Canada have realized the importance of participants in this specialist medical education program both as students as well as workers. But in Indonesia, it is only the status of a student. The purpose of this study is to further examine the equality of rights between workers and participants in the doctor's education program. This study is a normative juridical research using the conceptual approach to legislation, and comparative approach. The results indicate that there are similarities in the elements contained in the employment agreement between the workers and participants of the specialist medical education program so that the specialist education program participants should also obtain status as workers other than students. Based on this, then in this study there are several suggestions by the author including the need for revisions in the status of students towards specialist medical education participants.AbstrakPeserta program pendidikan dokter spesialis merupakan salah satu aspek yang berperan penting dalam pembangunan nasional di bidang kesehatan. Hal ini tidak terlepas dari salah satu aspek dalam program pendidikan dokter spesialis yaitu pelayanan. Negara-negara lain seperti Amerika Serikat dan Kanada telah menyadari akan pentingnya peserta program pendidikan dokter spesialis ini sehingga status peserta program pendidikan dokter spesialis di kedua negara tersebut adalah sebagai mahasiswa sekaligus sebagai pekerja. Namun di Indonesia, hanya berstatus sebagai mahasiswa. Tujuan dalam penelitian ini adalah untuk meneliti lebih jauh persamaan hak-hak antara pekerja dengan peserta program pendidikan dokter. Penelitian ini merupakan penelitian yuridis normatif dengan pendekatan perundang-undangan pendekatan konseptual, dan pendekatan perbandingan. Hasil penelitian menunjukkan bahwa terdapat persamaan unsur-unsur yang terkandung dalam perjanjian kerja antara pekerja dan peserta program pendidikan dokter spesialis sehingga peserta program pendidikan dokter spesialis seharusnya juga memperoleh status sebagai pekerja selain mahasiswa. Berdasarkan hal ini, maka dalam penelitian ini terdapat beberapa saran oleh penulis diantaranya adalah perlu adanya revisi dalam status mahasiswa terhadap peserta pendidikan dokter spesialis.